Crop Water Use and Irrigation Scheduling Guide for North Florida - Vivek Sharma; Charles Barrett; De Broughton; Thomas Obreza (EDIS)
Effective irrigation scheduling enables the irrigator to apply the right amount of water at the right time to meet the crop water demand. This 19-page guide presents information on average daily and weekly crop water use and crop growth stages for twelve north Florida crops that can be used to help schedule irrigation. This will allow a grower to develop a realistic irrigation schedule that minimizes plant water stress, saves water, and reduces nutrient leaching potential. Written by Vivek Sharma, Charles Barrett, De Broughton, and Thomas Obreza, and published by the UF/IFAS Department of Soil and Water Sciences, revised December 2020.